Development of an integrated healthcare model for diabetic patients in Nakhon Ratchasima Province - ตติยนันทพร, สุผล; สุระโคตร, ภูวเดช (Journal of Health Science of Thailand, 2025)
This action research aimed to (1) study the situation, problems, and solutions for diabetic patient care. (2) develop an integrated diabetic patient care model. (3) evaluate the development results of an integrated diabetic patient care model in Nakhon Ratchasima Province. The research sample was divided into 3 groups: (1) medical and public health personnel, 30 people; (2) diabetic patients, 272 people; and (3) related people, 96 people. The research instruments included document analysis, focus group discussions, questionnaires, and in-depth interviews. Quantitative data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation. Qualitative data were analyzed by classifying and grouping them. The research found that (1) all six districts had an increasing number of diabetic patients. The executives supported the establishment of diabetic schools in every district. The initial operation found a problem: diabetic patients did not see the importance of attending diabetic schools. In terms of solving the problem by explaining and clarifying to increase understanding. (2) The integrated diabetes care model in Nakhon Ratchasima Province has been developed in collaboration with all relevant sectors until the operational model was developed under the concept of the "Diabetes School Model," consisting of (2.1) diabetes schools (community, temple) and (2.2) diabetes patient families. (2.3) Diabetes clinic in SubDistrict Health Promoting Hospital (2.4) Diabetes clinic in a community hospital. (2.5) Province Health Board/District Health Board/SubDistrict Health Board/Village Health Board. (3) The evaluation of the integrated diabetes care model can be used in practice. The overall satisfaction of diabetic patients is at the highest level (=4.25, S.D. =.62). Diabetic patients can reduce or stop taking medication and are in a state of remission. The recommendation is that there should be a policy to establish diabetes schools at the district and national levels and to establish a diabetes college.